A Case Report of Idiopathic Ketotic Hypoglycemia Masquerading as Epilepsy - Dudipala, Sai Chandar; Battu, Krishna Chaithanya; Mandapuram, Prashanthi; Ch, Laxman Kumar (Journal of Pediatric Epilepsy, 2020)
Idiopathic ketotic hypoglycemia (IKH) is characterized by recurrent neurohypoglycemic symptoms with ketosis. Hypoglycemic episodes typically occur during early mornings, especially either with illness and/or prolonged fasting. We reported a case of IKH which presented with recurrent episodes of seizures during early morning with intercurrent illness and which was labeled as epilepsy and started on antiepileptic medication. The purpose of this case report is to alert clinicians about this condition, which is not an uncommon entity, but rarely thought of. Therefore, in view of keeping the IKH in mind, which can be prevented with proper diet advice during illness, unnecessary long-term antiepileptic therapy can be avoided.
Keywords: idiopathic ketotic hypoglycemia; epilepsy; diet advice